Can We Reduce Workplace Fatalities by Half? - David Soo Quee Koh (Elsevier, 2012)
Singapore, an island republic of over 5 million inhabitants, has 3.1 million workers. Most are employed in the service, finance and tourist/transport industry. Significant numbers work in manufacturing, construction and heavy industry. Following a series of construction and shipyard accidents with multiple deaths in 2004, the government announced its intention to reduce workplace fatalities from 4.9 to 2.5 per 100,000 by 2015. There was strong political will to achieve this target. The strategic approaches were to build workplace safety and health (WSH) capabilities; implement legislative changes with enforcement; promote benefits of WSH and recognize best practices, and enhance partnership with stakeholders. The anticipated outcomes were to reduce workplace fatality and injury rates; have WSH as an integral part of business; and establish a progressive and pervasive WSH culture. With these measures, the workplace fatality rate declined from 4.9/100,000 in 2004, to 2.2/100,000 in 2010. However, other confounding factors could also account for this decline, and have to be considered. The next target, announced by Singapore's Prime Minister in 2008, is to further reduce the workplace fatality rate to 1.8/100,000 by 2018, and to have "one of the best workplace safety records in the world".